Superior laryngeal nerve injury after thyroid surgery: One complication to reflect - Ribeiro, Daniela (2013)
Objectives: To evaluate the incidence of injury to the Superior Laryngeal Nerve (SLN) in patients who underwent laryngeal electromyography (LEMG) after thyroid surgery, to compare these results with the video-laryngo-stroboscopy (VLS) and observe their clinical course.Study Design: Retrospective consultation of medical records.Material and Methods: Patients underwent LEMG in our service after thyroid surgery. Characterization of age, sex, LEMG, VLS and clinical outcome.Results: Twenty-five patients were submitted to LEMG, with confirmation of SLN injury in 7/25 (28%). In 6 patients with SLN injury was observed concomitant lesion of the RLN, bilaterally in two cases. The VLS showed clinical signs of injury to the SLN in all cases diagnosed in LEMG. 42.8% of patients recovered the deficit caused by injury SLN up to 12 months after surgery.Conclusions: The risk of iatrogenic injury of the SLN is significant and should not be underestimated.